IMPLEMENTASI MEDIA POWERPOINT UNTUK PENINGKATAN KEMAMPUAN MENYIMAK BAHASA ARAB PADA SISWA KELAS VII DI SMP AL-MUHAIMIN - Fatihatul Muflihah; Reza romansah, Raudina rihadatul’aisi, Wahyu Hidayat, Dina Indriana (CV. ADIBA AISHA AMIRA, 2025)
This study examines the effectiveness of using PowerPoint media to improve Arabic listening skills among seventh-grade students at SMP Al-Muhaimin. The motivation for this research stems from the low listening skills in Arabic among students due to the lack of relevant learning media, monotonous teaching methods, and limited exposure to the Arabic language. This study employs a quantitative approach with an experimental method, using a pretest-posttest control group design. Two groups of students, an experimental group and a control group, were given a pretest to measure their initial listening skills. The experimental group was taught using PowerPoint media for 4-6 sessions, while the control group used conventional methods. After the learning sessions, both groups were given a posttest to measure the improvement in their listening skills.